1+1≥2? Norbornadiene‐Azobenzene Molecules as Multistate Photoswitches. Issue 2 (9th September 2020) - Kunz, Anne; Wegner, Hermann A.
Abstract: By combination of two photochromic molecules as multistate photoswitches new properties regarding to molecular solar thermal (MOST) energy storage systems and information storage capacity of smart materials are expected. By fusing the azobenzene with the norbornadiene system, new multinary photoswitches were designed. A successful synthesis towards different analogues was developed via Suzuki coupling reaction as key step. The isomerization behaviour of these norbornadiene‐azobenzene fusions was studied by UV‐Vis and 1 H NMR spectroscopy in different solvents investigating the electronic communication within these multinary‐photochromic systems. Abstract : One way or another : Two different photochromic units, azobenzene and norbornadiene, were connected as new multinary photoswitches. The successful synthesis of different analogues was achieved by using the Suzuki coupling reaction as the key step. The isomerization behavior was studied by UV/Vis absorption and 1 H NMR spectroscopies investigating the electronic communication within these multinary photochromic systems.